If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4x = -41 Solving 3 + 4x = -41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4x = -41 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = -41 + -3 4x = -41 + -3 Combine like terms: -41 + -3 = -44 4x = -44 Divide each side by '4'. x = -11 Simplifying x = -11
| 10x+1.25=100 | | b-7(4b-1)+b= | | -15+r=-8 | | -2m+4m-7=9 | | 3j+5k+3j+8k= | | 2x^3-8x^2+8x-6=0 | | -2x+25=3x-6 | | 4x+5968*3=0 | | C+4c=-90 | | mx^2-2x-m-1=0 | | 6x-10=-34 | | 7ab+ab-9ab= | | 0.66a=6 | | 3x+0+8=0 | | 3x^3-13x^2+12x-6=0 | | 9x-7y=y | | 10x-y=12 | | X+.75y=15 | | -(8-b)+12b-9=-6b+2b | | 1=x-6 | | 3(2x-1)+2=5x-1 | | x+4y+2z=0 | | 2x-3y+2=2 | | 6+4a=-8 | | 0.66r=8 | | 72=-3(x+4)-21x | | K-7=10 | | 3+z=18 | | 1.5r=8 | | -5x=18-3x | | 0.8m=80 | | -6+4y=-12 |